CONTINUITIES AND BREAKS AROUND SOCIAL JUSTICE DURING THE FIRST PERONISM IN SANTIAGO DEL ESTERO (1943-1955) - Erbetta, María Cecilia (Revista de Historia Social y de las Mentalidades, 2011)
In this paper we propose to analyze the  Peronism in the province of Santiago del  Estero from a look that tries to uncover the  way in which the spaces provincial and  national interlaced between 1943 and 1955,  and to place its particularity among old and  new. In other words, we believe that the  political space santiagueño, hegemonized  by Peronism almost from its irruption as  such, has a dynamic in which the spatial  boundaries between national and provincial  level, and temporal, between past and  present, are re-meant and rewrite in a  permanent way around the Social Justice.  The principal aim is realize of the scopes  that had the work justice across the  functioning of public organisms (office,  department, delegation and Work Courts)  in relation, in turn, with other institutions  from which there is revealed the principles of  social justice as the Peronism conceives them  during this period.
Keywords: Peronism; Hegemony; Social Justice; Work Courts